The Commodity Structure of Anglo-Irish Trade - McGilvray, James; Simpson, David (The Review of Economics and Statistics, 1973)
T RADITIONAL theories of international trade have explained the existence and composition of trade between countries in terms of international differences in production functions and factor endowments. More recently, increasing attention has been paid to other influences, which lie at the fringe of the traditional theory. These include the specific character of factors such as natural resources, the influence of tariffs and other restrictions on trade, and differences in size of country. Empirical studies of the composition of international trade have tended to test hypotheses about only a single one of these determinants. Yet it seems unlikely that they are mutually exclusive; one should expect several different influences simultaneously to play a part in shaping any given flow of trade. Accordingly, we have carried out an analysis of a particular trade flow to try to assess their relative empirical importance. The specific trade flow with which we are concerned is that between the Republic of Ireland and the United Kingdom. We have chosen to analyse this trade flow for the following reasons: First, we are fortunate to have detailed data on the flows of merchandise trade between Ireland and the United Kingdom. This information can be linked to the input-output tables of each country, which are comparable at a classification level of forty-seven sectors. We also have detailed and reliable estimates of Irish factor endowments.' Secondly, Irish trade with the United Kingdom forms a large part of her total trade (70 per cent of merchandise exports, and 50 per cent of merchandise imports in 1964). Exports from individual Irish sectors of production frequently account for a large share of sector output, while imports generally form a high proportion of the output of the domestic sector with whose products they are competing. Thirdly, the Irish economy is a small tradedependent economy whose exports have a large primary commodity content. The composition of its trade with its much larger and industrialised trading partner may not be untypical of the position in which so many developing countries find themselves with respect to their more advanced trading partners. It is worth emphasising that the small trade-dependent economy is typical of the great majority of countries. We begin with an empirical test of the Ricardian hypothesis of comparative advantage in its classical two-country, multi-commodity formulation. In the second section of the paper, we present the results of a number of tests concerned with hypotheses about factor proportions. The third section examines the influence of natural resources, and the paper concludes with an account of the role of trade restrictions.